Increase in use of root and tuber crops - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Although many root and tuber crops are considered to be poor people's crops, the consumption as well as the production of some of these crops has been increasing. Whilst yam and taro production in the Pacific has declined, according to a study by...